2012
DOI: 10.1103/physrevlett.108.032501
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Low-ZShore of the Island of Inversion atN=19

Abstract: The technique of invariant mass spectroscopy has been used to measure, for the first time, the ground state energy of neutron-unbound 28 F, determined to be a resonance in the 27 F + n continuum at 220(50) keV. States in 28 F were populated by the reactions of a 62 MeV/u 29 Ne beam impinging on a 288 mg/cm 2 beryllium target. The measured 28 F ground state energy is in good agreement with USDA/USDB shell model predictions, indicating that p f shell intruder configurations play only a small role in the ground s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 34 publications
3
38
1
Order By: Relevance
“…A 28 keV resonant decay from 25 F was assigned to a 1/2 − excited state in 25 F at an excitation energy of 4249 keV [8]. In the present paper we report the observation of the unbound ground state of 28 F and an unbound excited state in 27 F. The results of the 28 F experiment have been reported in a recent article [9].…”
supporting
confidence: 68%
See 3 more Smart Citations
“…A 28 keV resonant decay from 25 F was assigned to a 1/2 − excited state in 25 F at an excitation energy of 4249 keV [8]. In the present paper we report the observation of the unbound ground state of 28 F and an unbound excited state in 27 F. The results of the 28 F experiment have been reported in a recent article [9].…”
supporting
confidence: 68%
“…The overall resolution and acceptance for the decay of 28 F into 27 F + n has already been presented in Ref. [9], and the corresponding shapes are essentially identical in the case of 27 F * breakup. Due to the low statistics of the present data set, an unbinned maximum likelihood technique was used for parameter estimation [29].…”
Section: Modeling and Simulationmentioning
confidence: 76%
See 2 more Smart Citations
“…Previously, the Coulomb excitation studies of 32 Mg also confirmed the large deformation and pointed out the vanishing of the N = 20 shell gap [6]. The concept of island of inversion has been explored, for instance, experimentally also to isotones with N = 19 [7] and complementary information about its extent to at least N = 22 for the Ne isotopes was obtained [8].…”
Section: Introductionmentioning
confidence: 84%